Anatomy of breathing - Calais-Germain, Blandine (Eastland Press, 2006)
"Everyone breathes, yet few of us understand how to consciously control breathing to improve our well-being and the quality of many daily activities. 'Anatomy of Breathing' is a clear and helpful guide to both the theory and practice of breathing in its many variations. Hundreds of expert drawings along with easy-to-understand text help you explore just how breathing works. Once you're acquainted with the principal organs, structures, and forces that affect breathing, you will learn how to control them to enhance the quality and variety of breathing in your own life. Along the way, you will also correct many common misconceptions about breathing. 'Anatomy of Breathing' is filled with helpful practice pages. Here you will learn simple exercises to prepare your body for the benefits of different types of breathing. You will then be shown, step by step, how to practice some of the most common and useful breathing techniques on your own."--Publisher description.